Rumen Fermentation Characteristics and Methagenesis in Sheep Fed Silage-Based Diet Supplemented with Yucca Schidigera or Yucca Schidigera Combined with Nisin - Budi Santoso (Faculty of Animal Science, Universitas Gadjah Mada, 2004)
Artikel dalam bentuk PDF